Using the LM3 method to evaluate economic impacts of an on-line retailer of local food in an English market town. (February 2019) - Mitchell, Andrew; Lemon, Mark
The paper presents a case study of an on-line retailer of locally sourced food and drink to explore its local economic impacts on an English East Midland market town. The analysis is based on the LM3 survey method which tracks the value of an investment for a local economic area. While the findings suggest a positive impact, the reliability of third round data is disputed, and generates approximations rather than precise indicators of added economic value. In acknowledgement of this limitation, two approaches to working with round three data are compared. The paper concludes with recommendations for using this method in future research, as well as suggestions that might inform the development of a local or regional sustainable and resilient economic development policy framework.